Green Tea (Camellia sinensis) Products as Alternatives to Antibiotics in Poultry Nutrition: A Review - Steve Kgotlelelo Mahlake; Caven Mguvane Mnisi; Cebisa Kumanda; Doctor Mziwenkosi Nhlanhla Mthiyane; Peter Kotsoana Montso (MDPI AG, 2022)
The overuse and misuse of antibiotics in poultry feeds increase the total cost of production and compromise the quality of poultry products, which poses a serious threat to human health. Globally, health-conscious poultry consumers have long called for the alternate use of natural additives to mitigate the development and spread of multidrug resistant pathogens. Phytogenic plants, such as green tea (Camellia sinensis) products, contain putative nutraceuticals with antibiotic properties that can be used as alternatives to therapeutic, metaphylactic, prophylactic, and growth-promoting antibiotics. However, there are limited studies in the literature that have evaluated the potential of green tea (GT) products when used as replacements to in-feed antibiotics, with most studies focusing on their potential as sources of dietary nutrients in poultry feeds. Thus, this review paper discusses the potential of GT products to replace various antibiotics in poultry diets while presenting GT bioactive substances that can improve the growth performance, carcass and meat quality traits, and health status of the birds. We postulate that the utilisation of GT products in place of antibiotics could deliver sustainable, organic poultry production systems that would contribute significantly to global food and nutrition security.